2008
DOI: 10.1002/cta.551
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry‐aware placement algorithm using transitive closure graph representation for analog integrated circuits

Abstract: SUMMARYRecently several topological representations have been explored as alternatives to the conventional absolute-coordinate representation for integrated circuit layout automation. Those topological representations, however, lack one or more aspects in capturing the solution space subject to symmetry constraints, which are abundant in analog layouts.In this paper, we explore the use of transitive closure graphs (TCGs) to represent analog placements, i.e. placements with symmetry constraints. We define a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Hence, floorplanning [1][2][3][4][5][6][7] is a crucial step in VLSI circuit design [8] as it determines the quality of the deep submicron chip quality, manufacturing cost and the time-to-market. Hence, floorplanning [1][2][3][4][5][6][7] is a crucial step in VLSI circuit design [8] as it determines the quality of the deep submicron chip quality, manufacturing cost and the time-to-market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, floorplanning [1][2][3][4][5][6][7] is a crucial step in VLSI circuit design [8] as it determines the quality of the deep submicron chip quality, manufacturing cost and the time-to-market. Hence, floorplanning [1][2][3][4][5][6][7] is a crucial step in VLSI circuit design [8] as it determines the quality of the deep submicron chip quality, manufacturing cost and the time-to-market.…”
Section: Introductionmentioning
confidence: 99%
“…The number of transistors in a very-large-scale integration (VLSI) chip design has increased rapidly, and the features of integrated circuits have progressively scaled down nowadays. Hence, floorplanning [1][2][3][4][5][6][7] is a crucial step in VLSI circuit design [8] as it determines the quality of the deep submicron chip quality, manufacturing cost and the time-to-market. Although there are several circuit design objectives to be considered during floorplanning, such as area minimization, wirelength optimization [9], delay reduction [10,11], thermal stability [12][13][14], clock tree synthesis [15] or any combination of these objectives [16][17][18], the basic objective of floorplanning is to minimize the area of the VLSI chip.…”
Section: Introductionmentioning
confidence: 99%
“…The objective is to minimize the area and wire length with the fixed‐outline constraint. After partitioning , the relative location of the different modules needs to be decided before the placement stage (i.e., placing the cells in the relative location), with the objective of minimizing the total area occupied by the components. The floorplanning problem has been proved to be Non‐deterministic Polynomial‐time (NP) hard .…”
Section: Introductionmentioning
confidence: 99%
“…

Multi-voltage techniques are being developed to improve power savings by providing lower supply voltages for noncritical blocks under the performance constraint. With exploding design complexity, it is necessary to consider voltage drop issues in the early design cycle [14][15][16][17]. For voltage drop optimization, both block and power pad positions are important factors that need to be considered.

…”
mentioning
confidence: 99%
“…However, those techniques are implemented only when the floorplan or placement is ready. With exploding design complexity, it is necessary to consider voltage drop issues in the early design cycle [14][15][16][17]. Once the voltage drops aware floorplan is obtained, the detailed P/G network design can be performed in the subsequent placement and routing stages that consider Steiner tree construction and electromigration issues [18,19].It is reported that 5% of voltage decrease may cause the circuit performance slowdown up to 15% or more [20].…”
mentioning
confidence: 99%